2016
DOI: 10.1016/j.juro.2015.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Sarcopenia in Patients with Metastatic Renal Cell Carcinoma

Abstract: Sarcopenia is a significant prognostic factor in metastatic renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 25 publications
3
84
3
2
Order By: Relevance
“…These results indicated that sarcopenia may be a significant predictor of prognosis in patients with HCC who underwent sorafenib therapy, and potentially in patients with other types of malignancies. Individualized nutritional assessment and interventional strategies may be recommended for patients with HCC and sarcopenia treated with sorafenib (18,24,25). By contrast, it should be noted that sarcopenia was identified in 151 (65.1%) patients in the present analysis.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These results indicated that sarcopenia may be a significant predictor of prognosis in patients with HCC who underwent sorafenib therapy, and potentially in patients with other types of malignancies. Individualized nutritional assessment and interventional strategies may be recommended for patients with HCC and sarcopenia treated with sorafenib (18,24,25). By contrast, it should be noted that sarcopenia was identified in 151 (65.1%) patients in the present analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, sarcopenia has attracted a high level of attention in the fields of several types of malignancies due to its impact on clinical outcomes (18,24,25). However, to the best of our knowledge, reliable data regarding the impact of sarcopenia on the clinical outcomes of patients with HCC receiving sorafenib therapy have yet to be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia is a commonly observed disorder in aged populations and is associated with disability, functional decline and frailty (13,14). Age-associated sarcopenia is defined as primary sarcopenia, whilst advanced malignancies, as well as chronic inflammatory diseases including renal, heart and liver diseases, can be the causes of secondary sarcopenia (12)(13)(14)(15)(16). Severe underlying diseases can lead to sarcopenia and cachexia, which involves body weight loss and muscle wasting.…”
Section: Effect Of Pretreatment Psoas Muscle Mass On Survival For Patmentioning
confidence: 99%
“…10 In RCC, sarcopenia has been recently studied, in patients with localized 11 , and metastatic disease. 12, 13 …”
Section: Introductionmentioning
confidence: 99%